Kualitas Pelayanan dan Keputusan Berkunjung di Atraksi Alam dan Buatan Malalayang Beach Walk Kota Manado - Christine P. E. Porajow; Steven Y. Kawatak; Yelly A. Walansendow; Dheanie Z. O. Anggoh (Yayasan Literasi Sains Indonesia, 2023)
Malalayang Beach Walk is a new leading destination in Manado City which is unique because it is a combination of natural tourist attractions and artificial tourist attractions. This tourist destination is located along the coast on the Trans Sulawesi route which is heavily traveled by local residents and immigrants from various other areas. This destination is known to have an important social and economic influence on the local community, so maintaining good and consistent service quality at this destination is the right step. This research was carried out with the aim of finding out how strong the influence of service quality is on tourists' visiting decisions at Malalayang Beach Walk. The data in this study was obtained from 100 respondents selected using accidental sampling technique. The data obtained was then processed using a quantitative approach through SmartPLS 3.0 analysis. The research result shows that service quality has a strong and significant influence on tourists' decisions to visit Malalayang Beach Walk.